Diversity of forest floor vegetation in Napabalano Nature Reserve and Warangga Protection Forest, Southeast Sulawesi - Sulistijorini Sulistijorini; Ilma Rahmawati; Ibnul Qayim (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.